From Local Resources to Economic Resilience: Pandan-Lime Dish Soap as a Catalyst for Rural Prosperity - Kesuma, Muhammad Ramadhani; Ramadhan, Gholib Murtadho; Pangestu, Gary (Indo Publishing, 2025)
This qualitative case study explores the economic potential of pandan-lime dish soap as a driver of rural resilience in Desa Sesulu, East Kalimantan, Indonesia. Utilizing in-depth interviews with 30 respondents, participatory observations during simulated production, and document analysis, the study examines how local resources foster sustainable economic practices. Thematic analysis reveals key insights: the production of natural dish soap reduces household costs by leveraging abundant pandan leaves and limes, promotes entrepreneurial opportunities through home-based enterprises, and enhances environmental awareness by minimizing chemical pollution. However, logistical barriers, such as limited access to materials like Texapon, and socio-economic challenges, including skepticism about efficacy, hinder adoption. The findings highlight the initiative’s alignment with circular economy principles, offering a model for cost-effective, community-driven innovation. Recommendations include material subsidies and digital literacy training to enhance scalability. This study contributes to the discourse on green economy practices by demonstrating how grassroots initiatives can bolster economic resilience and sustainability in rural contexts, with implications for policy and practice in achieving responsible consumption and economic growth.